CORRELATION BETWEEN DIFFERENT MOTOR ABILITIES AND SCORE POINTS IN THE RAUCH CUP - Špela Bogataj; Blaž Lešnik (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2018)
In alpine skiing like in other sports, achieving good results depends on a variety of factors and the quality of planning and conducting the process of training. The purpose of the research was to determine whether there is a correlation between selected motor tests and the number of points achieved in Rauch Cup. The research was conducted on a sample of 41 male competitors from different ski clubs across Slovenia. The following tests were conducted on our selected group of 13 - 14 year old males: taping with a dominant leg, test of stability, run from a flying start (maximum speed), ten jumps on both legs, 400m run, running nines, counter movement jump and reaction time to a visual impulse (squat jump). The linear regression analysis was used to determine the relationship between selected motor tests and performance in alpine skiing (Rauch Cup points). Correlation was found between each individual motor test and criterion variable (Rauch Cup points) except test of stability and reaction time test (squat jump). Multiple linear regression (MLR) showed us that the selected model, assembled of four tests that gave the highest MLR was significant (R=.727; p < .001). According to the findings, we can conclude that motor skills represent 53% of the competitive performance variance of the alpine skier.